Clarity, Covenants, and Calvin's Divine Accommodation: Pedagogical Foundations for Christian Education - Gunter, Nathan H. (Christian education journal, 2018)
This article argues that the doctrine of the clarity of Scripture strengthens the pedagogical example provided by progressive covenantalism, as articulated by Stephen Wellum, and the concept of divine accommodation, as articulated by John Calvin. The intersection of these theological concepts provides a mutually reinforcing vision for the pattern and practice of pedagogy as revealed through the clear teaching of Scripture.